2020
DOI: 10.1109/access.2020.2984311
|View full text |Cite
|
Sign up to set email alerts
|

Modified Elman Spike Neural Network for Identification and Control of Dynamic System

Abstract: The utilization of conventional modeling strategies in the identification and control of a nonlinear dynamical system suffers from some weaknesses. These include absence of precise, conventional knowledge about the system, a high degree of uncertainty, strongly nonlinear and time-varying behavior. In this paper, a modified training algorithm for the identification and control of a nonlinear system using a soft-computing approach is proposed. Specifically, a modified structure of the Elman neural network with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The experimental results showed that,the proposed algorithm is more efficient than the other algorithms in terms of minimizing the distance and maximizing the speed for reaching to target. There are a lot of algorithms that are proposed by the researchers to empower the ability of AI to fast train with high quality of adaptation in variety applications [19][20][21][22][23] .…”
Section: Related Research Workmentioning
confidence: 99%
“…The experimental results showed that,the proposed algorithm is more efficient than the other algorithms in terms of minimizing the distance and maximizing the speed for reaching to target. There are a lot of algorithms that are proposed by the researchers to empower the ability of AI to fast train with high quality of adaptation in variety applications [19][20][21][22][23] .…”
Section: Related Research Workmentioning
confidence: 99%
“… Then, the extracted features are transferred to enhanced Elman spike neural network (EESNN) [19] classifier for classifying the authorized person and unauthorized person.Then the weight parameters of the EESNN are optimized using the Glowworm swarm optimization Algorithm (GWO) [20].…”
Section: Introductionmentioning
confidence: 99%
“…In this article, the deep learning methodology is outlined and it reveals how the nodes are classified as malicious and harmless. For a node, classification can be used for determining the difficulty of a given PoW 20‐28 …”
Section: Introductionmentioning
confidence: 99%
“…To improve the security of the IoT devices, the blockchain based deep learning methodology is used in this work. The major contributions of this work is summarized below: Enhanced Elman spike neural network (EESNN) with green proof of work consensus algorithm (GPoW) based coalition formation (CF) mechanism (EESNN‐GPoW‐CF) is proposed for improving the security of the IoT network. Initially, an EESNN 24 is proposed for categorizing the devices as malicious and benign on internet of things network. Moreover, ensuring the problems of scalability uses blockchain‐based mechanism named as GPoW consensus algorithm 25 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation